2019
DOI: 10.1007/s00402-019-03302-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after thumb carpometacarpal joint stabilization with an abductor pollicis longus tendon strip for the treatment of chronic instability

Abstract: Introduction Instabilities of the thumb carpometacarpal (CMC) joint, caused by idiopathic ligamentous hyperlaxity, trauma or other conditions may lead to pain, functional impairment and eventually osteoarthritis. Several techniques have been described to enhance stability of the CMC 1. The aim of this study was to evaluate postoperative outcomes after CMC 1 joint stabilization using a soft-tissue procedure in patients with chronic instability. Materials and methods This study was designed as a retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…If LR had failed, CMC arthrodesis would have been an appropriate salvage procedure. It has been shown to provide a high level of patient satisfaction and symptomatic relief in patients with chronic, painful laxity, and it might have been considered 9 Ultimately, this case, in conjunction with the literature review, emphasizes early treatment and postreduction stability assessment, with LR, in the setting of long-term instability.…”
Section: Discussionmentioning
confidence: 86%
“…If LR had failed, CMC arthrodesis would have been an appropriate salvage procedure. It has been shown to provide a high level of patient satisfaction and symptomatic relief in patients with chronic, painful laxity, and it might have been considered 9 Ultimately, this case, in conjunction with the literature review, emphasizes early treatment and postreduction stability assessment, with LR, in the setting of long-term instability.…”
Section: Discussionmentioning
confidence: 86%
“…Edmunds (2006) postulate that acute isolated dislocations of TMCJ requires open ligamentous reconstruction either by direct suturing or by tenodesis of the TMCJ using graft as flexor carpi radialis tendon [22] . Published treatment modalities, regarding tendon graft for reconstruction of TMCJ dislocation, included flexor carpi radialis tendon (FCR), Abductor pollicis longus (APL), Palmaris longus (PL) and most recently Extensor carpi radialis longus (ECRL) [6,17,31,32] . Eaton et al first introduced FCR tendon graft as an advantage of near location of the tendon to dislocated site and the ability to correct the hypermobility of the TMCJ (reconstruct the palmar ligament and reinforced dorsal capsule).…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al (2014) first implement CMC joint suspension arthroplasty and report improved pinch and grip strength and painless function of the thump [32] . Stauffer et al (2020) used as tendon graft APL and reported in 15 operated thumbs that postoperative grip, pinch strength, and passive stability were not significantly different between operated and non-operated sides while Mean DASH score was 13.3 and VAS 1,1 [31] . Kim et al (2021) in a systematic review 85% report that most common tendon graft which utilize was FCR (57%) following by APL (29%) and all studies with this two methods prove normal range of motion without posttraumatic instability sustainment the effectiveness of the two methods [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to several studies of CMC arthroplasty utilizing the modified FCR LTRI technique in the literature reporting good mid-term to short-term outcomes. [15][16][17] Tomaino et al 18 reported on long-term outcomes including radiographic assessment of LRTI in 24 thumbs at long-term follow-up. Relief of pain was seen in 95% of patients.…”
Section: Expected Outcomesmentioning
confidence: 99%